Regional Horizontal Networks within the SME Agri-Food Sector: An Innovation and Social Network Perspective. Issue 8 (2nd August 2016) - McAdam, Maura; McAdam, Rodney; Dunn, Adele; McCall, Clare
Abstract : Mc Adam M., Mc Adam R., Dunn A. and Mc Call C. Regional horizontal networks within the SME agri-food sector: an innovation and social network perspective, Regional Studies . This paper aims to explore how regional horizontal networks within the small and medium-sized enterprise (SME) agri-food sector develop innovative capability and outcomes through the adoption of a combined innovation and social network perspective. To facilitate this, the Slow Food Network was deemed appropriate. A multiple case analysis was then used in order to explore 11 regional SME-based agri-food horizontal networks. The findings demonstrate that a complex life cycle development occurred within the regional SME networks. Such development required unique strategies of explorative and exploitative innovation-based knowledge exchange at different life cycle stages with resultant changes in network dynamics between the SMEs.